A Step-by-Step Guide to Fully Percutaneous Transaxillary Transcatheter Aortic Valve Replacement. Issue 5 (2nd November 2017) - Mathur, Moses; Krishnan, Sandeep K.; Levin, Dmitry; Aldea, Gabriel; Reisman, Mark; McCabe, James M.
ABSTRACT: Transcatheter aortic valve replacement (TAVR) is now established as a viable therapy for the treatment of severe aortic stenosis. Though femoral access is used for the majority of cases today, this approach may be limited in cases of insufficient vessel caliber, tortuosity or severe iliofemoral disease. For such scenarios, a transaxillary (TAx) approach is appealing as this vessel appears to be far less frequently affected by atherosclerotic disease, even in the presence of significant iliofemoral disease. Though surgical cut-down has been the traditional method for the TAx approach, there has been a growing clinical experience with successful percutaneous transaxillary access in the setting of TAVR and mechanical circulatory support devices. In this review, we offer a step-by-step guide to TAx TAVR.